FORMULATICITY OF THE INCOMPLETE SYNTACTIC FORM OF AN IMPERATIVE STATEMENT IN DISCOURSE - Iuliia А. Nenasheva (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. Language units functioning in specific discourse conditions undergo desemantization and gramaticalization, which results in new discourse units forming. These units perform relevant discourse functions and carry communicative meanings. These units also possess formulaicity due to pragmatic factors. Corpus analysis provides proper techniques to identify and describe these units, classify factors conditioning the appearance of such units in discourse.